1983
DOI: 10.1007/bf01870797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an outward water flow on potassium currents in a squid giant axon

Abstract: The excitation of the squid giant axon was analyzed under an outward water flow through the membrane product by an osmotic gradient. The outward water flow made an undershoot of the action potential larger by about 25 mV without decreasing its peak largely. It also made EK more negative but not ENa. The effect of the outward water flow was specific for the potassium channel. The outward current increased and its decline during a long-lasting depolarization became less prominent under the outward water flow. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this study, an attempt has been made to prevent K+ accumulation by outward water flow maintained by an osmotic gradient across the axolemma. In a previous paper, it was reported that the outward osmotic water flow increased the undershoot of the action potential and the outward K+ current under voltage clamp and decreased the inward tail K+ current (Kukita & Yamagishi, 1983). In this paper, it is demonstrated that these effects were mainly due to the removal of K+ accumulation in the periaxonal space.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, an attempt has been made to prevent K+ accumulation by outward water flow maintained by an osmotic gradient across the axolemma. In a previous paper, it was reported that the outward osmotic water flow increased the undershoot of the action potential and the outward K+ current under voltage clamp and decreased the inward tail K+ current (Kukita & Yamagishi, 1983). In this paper, it is demonstrated that these effects were mainly due to the removal of K+ accumulation in the periaxonal space.…”
Section: Introductionmentioning
confidence: 60%
“…Hypertonic conditions without water flow neither change the shape nor amplitude of the action potential, nor the ionic currents, except for the time courses and conductances (Kukita & Yamagishi, 1979;Kukita, 1982). However, when an outward water flow was induced, K+ currents changed (Kukita & Yamagishi, 1983) and here changes are ascribed to the elimination of K+ accumulation in the periaxonal space. K+ accumulation may not be removed by a mere shrinkage of the Schwann cells because the application of hypertonic solutions did not eliminate K+ accumulation unless the outward water flow was induced by creating an osmotic gradient (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Ion channels are pores and may be able to pass water as well as ions (Kukita & Yamagishi, 1983). In characean ceils, it is known that pores exist that pass water, but not ions (Kiyosawa & Ogata, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The time to peak of the undershoot from the beginning of the action potential train did not alter. the external solution is doubled by the addition of a nonelectrolyte, producing efflux of water across the axonal membrane and presumably contraction of cells surrounding the giant fibre (Kukita & Yamagishi, 1983;Kukita, 1988;. Figure 2 shows an example of K+ currents evoked by stepwise depolarizations of different duration.…”
Section: Properties Of Action Potential Trainsmentioning
confidence: 99%